Low glycemic CHO ingestion minimizes cognitive function decline during a simulated soccer match - Quinones, M. D.; Lemon, P. W. R. (International Journal of Sports Science & Coaching, 2022)
Often cognitive function is affected adversely during prolonged, high intensity exercise. We assessed whether hydrothermally modified corn starch (HMS) ingestion minimizes cognitive decline with soccer play. 11 men (177.7 ± 6.8 cm, 77.3 ± 7.9 kg, 22 ± 3 y, 12.8 ± 4.9% body fat, V O2max = 57.1 ± 3.9 ml kg BM 1 min 1; mean ± SD) completed 60 min simulated soccer matches with HMS (8% CHO; 0.7 g kg BM 1 h 1; 2.8 kcal·kg BM 1 h 1) vs isoenergetic dextrose (DEX) consumed 30 min prior to the match and at half time. Compared to DEX, blood glucose was lower (p < 0.001) with HMS at 15 (5.3 ± 0.6 vs 7.7 ± 1.4 mmol L 1) and 30 min post ingestion (5.6 ± 0.6 vs 8.3 ± 1.0 mmol L 1), and greater (p = 0.004) after 15 min of play (5.8 ± 0.5 vs 5.1 ± 0.6 mmol L 1). With HMS, perceived exertion ratings were reduced throughout the match (p = 0.025 at 15 min). Flanker test incongruent trial reaction time (p = 0.040) and conflict cost (p = 0.019) were both better with HMS. These data suggest that HMS ingestion minimizes cognitive decline during soccer play. More study is warranted to elucidate fully the cognition benefits of HMS ingestion for sport performance.